Erosivity and rainfall patterns for Pirenópolis, Goiás, Brazil - Rezende, Cássia Cristina; Machado, Roriz Luciano; Andrade, Aline Franciel de; Silva, Talles Victor; Ferreira, Elizabete Alves; Buso, Wilian Henrique Diniz (Journal of Agricultural Studies, 2022)
Water erosion is one of the biggest environmental problems, causing a reduction in agricultural productivity and compromising the quality and quantity of water resources. Therefore, the development of researches that help in the planning of land use and management aiming at sustainable agriculture is a necessity in the state of Goiás. This work was carried out with the objectives of analyzing the annual distribution of rainfall erosivity, determining the factor erosivity of rain (R fator) of the universal soil loss equation (USLE) and the rainfall patterns of Pirenópolis - Goiás (GO). A pluviographic series from the period from 2002 to 2007 and a rainfall series from 1986 to 2014 were used. Data were analyzed in a completely randomized design in a 7 (months) x 3 (patterns) factorial scheme. Through the results, it was possible to verify that: the erosive potential was concentrated between the months of October and April, corresponding to 94.2% of the average annual to index EI30. The factor R of the USLE for the locality of Pirenópolis - GO was 7,799.5 MJ mm ha-1 h-1 year-1, and 130.2 MJ ha-1 year-1, for the index KE> 25. The advanced hydrological pattern was the most frequent among the analyzed precipitations, followed by the delayed and intermediate patterns. According to the analysis, the intermediate pattern presents higher erosivity values for individual precipitation events for the months of November, December and April.